ANALISIS HUKUM ISLAM TENTANG PELANGGARAN PERJANJIAN PERKAWINAN - St. Habibah (Al-Bayyinah, 2017)
AbstractA marriage agreement in a marriage bond becomes important if it is actually exercised by the husband and wife and upon mutual agreement. However, the marriage covenant is not always obeyed by the husband and wife or there is a violation in it. The consequences if there is a breach of the marriage agreement whether under Islamic law or positive law is the husband or wife who feels aggrieved over the offense may file a lawsuit either purely civil or place the breach of the agreement as a reason for divorce as in Article 51 Compilation The Islamic law states "Violations of the Marriage Agreement give wife rights for the cancellation of marriage or to propose as a reason for divorce to the Religious Courts.Kata Kunci: Pelanggaran Perjanjian, Pernikahan, Hukum Islam